Antineutrophil cytoplasmic antibody-positive familial Mediterranean fever and hyperthyroidism: A case report - Segoe, Sorato (Medicine (Baltimore), 2018)
RATIONALE: Familial Mediterranean fever (FMF) is a genetic autoinflammatory disorder characterized by serositis and recurrent fever. Previous reports identified patients with antineutrophil cytoplasmic antibody (ANCA)-positive FMF, but vasculitis symptoms were not reported. PATIENT CONCERNS: We report the case of a 44-year-old man with numbness. He had a history of 3 episodes of pleurisy and was being treated with propylthiouracil for hyperthyroidism. Because he was ANCA-positive, we suspected drug-induced ANCA-associated vasculitis and propylthiouracil was discontinued. However, his numbness was not ameliorated, and he again developed high fever with pleurisy. DIAGNOSIS: Diagnosis of FMF was finally made, and genetic analysis revealed compound heterozygous mutations in exon 2 of the familial Mediterranean fever gene (L110P/E148Q). INTERVENTIONS: The patient was treated with 0.5 mg/day of colchicine. OUTCOMES: His numbness improved, and fever has not recurred. LESSONS: Appearance of ANCA and development of vasculitis should be considered in a clinical course of FMF with hyperthyroidism.